PERBEDAAN ZONA HAMBAT CIPROFLOKSASIN DENGAN EKSTRAK KURMA (Phoenix dactylifera) TERHADAP BAKTERI GRAM NEGATIF SECARA IN VITRO - Masfiyah, Masfiyah; Rahayu, Rahayu (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2019)
Date palm fruit (Phoenix dactylifera) is a fruit that has many benefits such as antioxidant,anti-bacterial, and anti-cancer effects. Dates also contain phytochemicals such aspolyphenols (flavonoids, isoflavones, lignin and phenolic acids), tannins, carotenoids, andsterols. This study aims to determine the activity of ciprofloxacin and dates (Phoenixdactylifera) against gram negative bacteria.This is an experimental laboratory research with a post-test only control groupdesign. Bacterial activity was assessed based on the diameter of the inhibition zone in MullerHinton agar with Kirby Bauer method. The gram-negative bacteria tested were Escherichiacoli and Klebsiella pneumoniae from clinical isolates that had been identified using VITEK®2. The concentration of the test bacteria was 0.5 Mac Farlan. The dates extract used wasAjwa dates extract ripe at 100% concentration using the socletation method with methanolsolvent. The test group was divided into 3 groups, namely the ciprofloxacin group only, theciprofloxacin group and the date palm extract, the date palm extract group only.There is no significant difference (P > 0.05) in the activity of ciprofloxacin andciprofloxacin with date palm extract against E. coli and Klebsiella pneumonia bacteria.There was no difference in the activity of ciprofloxacin or ciprofloxacin with theaddition of Ajwa date extract.